Analysis of Good Corporate Governance Implementation in BUMDes Management and Its Contribution to Village SDGs (A Study of BUMDes Surya Sejahtera, Kedungturi Village, Taman District, Sidoarjo Regency) - Achmad Bagas Djuan Rajendra; Taufiq Hidayat (Indonesian Journal Publisher, 2025)
This study aims to analyze the implementation of good corporate governance in the management of BUMDes and its contribution to the SDGs of the village at DUMDes Surya Sejahtera Kedungturi, Taman District, Sidoarjo Regency. This study uses a qualitative method with primary data obtained from the Secretary and Treasurer of BUMDes Surya Sejahtera. Data collection techniques include interviews, observation, and documentation. The results of the study show that BUMDes Surya Sejahtera has implemented GCG well, although improvements are needed in transparency, digital literacy, and community participation. GCG contributes positively to BUMDes performance, community economy, and achievement of Village SDGs.